2007
DOI: 10.1111/j.1742-4658.2006.05637.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of the membrane‐bound quinol peroxidase functionally connected to the respiratory chain

Abstract: Here, we report for the first time quinol peroxidase (QPO), an enzyme that uses ubiquinol‐1 as an electron donor for the reduction of H2O2 to water. We purified QPO to > 90% purity from the membrane fraction of Actinobacillus actinomycetemcomitans. QPO is a 53.6‐kDa protein that contains three heme c molecules. The qpo gene was predicted to encode a putative bacterial cytochrome c peroxidase with N‐terminal extensions containing an additional potential heme c‐binding motif. Although qpo has high sequence homol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 60 publications
(85 reference statements)
4
37
0
Order By: Relevance
“…Hydropathy analysis revealed that there is one possible membrane-spanning segment at the N-terminal (data not shown), which is responsible for association with the inner membrane. Although the N-terminal about 20-amino-acid sequence has a character of basic amino acids followed by a hydrophobic sequence, similar to that of a signal sequence, it may be not removed because a similar sequence is present in purified tri-heme CCP in A. actinomycetemcomitans [Yamada et al, 2007;Takashima et al, 2008]. This is consistent with the finding that most peroxidase activity in Z. mobilis was recovered in membrane fractions (see below).…”
Section: Structural Characteristics Of Zmcytcsupporting
confidence: 79%
See 3 more Smart Citations
“…Hydropathy analysis revealed that there is one possible membrane-spanning segment at the N-terminal (data not shown), which is responsible for association with the inner membrane. Although the N-terminal about 20-amino-acid sequence has a character of basic amino acids followed by a hydrophobic sequence, similar to that of a signal sequence, it may be not removed because a similar sequence is present in purified tri-heme CCP in A. actinomycetemcomitans [Yamada et al, 2007;Takashima et al, 2008]. This is consistent with the finding that most peroxidase activity in Z. mobilis was recovered in membrane fractions (see below).…”
Section: Structural Characteristics Of Zmcytcsupporting
confidence: 79%
“…ZmCytC in Z. mobilis has been annotated as CCP [Seo et al, 2005], though it seems to possess three heme cbinding motifs similar to ubiquinol peroxidase in A. actinomycetemcomitans [Yamada et al, 2007;Takashima et al, 2008]. In order to determine the physiological function of ZmCytC and its electron donor, ZmcytC -disrupted mutant was constructed and examined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The qpo gene encoding quinol peroxidase was also identified. The qpo gene is highly similar to ccpR, but the deduced amino acid sequence of qpo has three haem c-binding motifs while that of ccpR has two motifs (Yamada et al, 2007). The expression level of qpo was higher in cells grown on ethanol or the mix of ethanol and glucose, but significantly reduced in those grown on glucose (Fig.…”
Section: Differential Expression Of the Highly Branched Respiratory Cmentioning
confidence: 95%